Ensaio sobre as bases e os elementos de uma teoria dos precedentes judiciais - Bortolin, Luís Felipe Bombardi (2025)
It is common to find the discussion of judicial precedents in the courts, especially higher courts, based on an “efficiency” aspiration. By this, we mean that the discourse on precedents in recent years has been reduced to a claim to both contain the large number of mass and repetitive demands that plague the courts and stabilize case law, based on prefabricated legal solutions. This research aims to propose a democratic gain if judicial precedent is analyzed not only from the point of view of efficiency, but also as an important element in the justification of judicial decisions, which deserves its own theory. In search of the central elements of a theory of precedents, studies are carried out on the use of this source of law in other countries with different legal traditions, as well as debating the relationship between the two great Western legal traditions (common law and civil law). At the end of this investigation, it is concluded that the theory of precedents, in general, can be divided into a “basis” and some “elements” that make it up. With these conclusions in hand, we set out to study the different theoretical frameworks from which these questions could be critically answered. The aim is to demonstrate the main differences between the theoretical frameworks that can be adopted to deal with precedents, in addition to defending the idea that any thought proposed to be a theory of precedents needs to adopt a clear theoretical framework. It goes on to analyze the different proposals for a theory of judicial precedents in Brazilian law, concluding that if we want to effectively create a culture of respect for judicial precedents in Brazil, the best way to do so (i.e. the most democratic and theoretically grounded way) is through the Hermeneutic Critique of Law, as proposed by Professor Lenio Streck